Applicability of the harmonized in vitro digestion method to titanium dioxide nanomaterials - Alvito, Paula (2020)
Titanium dioxide nanomaterials (TiO2 NMs) have a high potential for ingestion by human populations, due to their increasing use as food additives, inclusion in dietary supplements and food packaging materials. Whether this oral exposure may lead to adverse local or systemic outcomes, has been the subject of research. In vitro studies have generated contradictory results, possibly due to differences in the physicochemical properties of the TiO2 NMs studied, which can be additionally affected by the surrounding matrix and interactions during digestion. INGESTnano is a national project aimed at investigating the nano-bio interactions of nanomaterials on intestinal cells, at the cellular and molecular levels, after the digestion process, to better understand their potential impacts on human health. Three TiO2 NMs were selected as case-studies to setup a workflow for addressing nanosafety concerns of ingested NMs, while considering the nano-bio interactions under physiological conditions. As an alternative to in vivo testing, this project is focused on the use of the harmonized in vitro digestion method for simulating the human digestion of NMs. This digestion comprises three compartments: a) mouth (pH 7.0, alpha-amylase, salts); b) stomach (pH 3, HCl, pepsin, salts) and c) small intestine (pH 7.5, bile salts, pancreatin, salts). The final product of digestion is tested in bioassays using intestinal cells, to ascertain its toxicity. A high level of toxicity of the final digestion product challenged the applicability of the digestion product in the biological assays. The results revealed that digestion products without the NM showed cytotoxic effects above the concentration of 10% in cell culture medium. Several modifications to the initial protocol were thus performed to overcome this issue. The results suggested that the addition of bile salts accounted for most of the toxicity observed. The applicability of the harmonized in vitro digestion method is discussed in view of its potential use as a tool for addressing the toxicity of ingested NMs or other food contaminants, mimicking the physiological processes, in alternative to animal models.